Transforming Cybersecurity Practices: A Comprehensive Approach to Protecting Digital Banking Assets - Zangana, Hewa; Mohammed, Harman Salih; Husain , Mamo Muhamad (PT. SNN MEDIA TECH PRESS, 2025)
The rapid evolution of digital banking has introduced unprecedented security challenges, necessitating a proactive and comprehensive cybersecurity framework. This paper explores advanced strategies for safeguarding digital banking assets, integrating cutting-edge technologies such as artificial intelligence (AI), blockchain, and zero-trust architectures. By analyzing emerging threats, regulatory requirements, and best practices, this study presents a holistic approach to strengthening financial cybersecurity resilience. The findings emphasize the need for a dynamic, multi-layered security model that adapts to evolving cyber threats while ensuring compliance and user trust.